2020
DOI: 10.1177/0017896920915594
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation of children’s environmental health questionnaires for nursing students in England

Abstract: Objectives: Children are among the most vulnerable population groups with regard to environmental risks. Nursing students must be fully educated on children’s environmental health as they are in a key position to prevent and reduce the effects of environmental hazards. The main objective of this study was to adapt and validate an English language version of two questionnaires about children’s health and the environment, to assess the knowledge and skills of student nurses in England. Design: Observational cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results of RSM analysis showed that the ChEHS‐Q model was well fitted. The reliability and separation index of the Chinese version of ChEHK‐Q and ChEHS‐Q are better than the previous Spanish version (Álvarez‐García et al., 2018) and English version (Álvarez‐García et al., 2020), which means that these two questionnaires can accurately measure the knowledge and skills of nurses in children's environmental health and classify nurses according to their latent traits appropriately.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The results of RSM analysis showed that the ChEHS‐Q model was well fitted. The reliability and separation index of the Chinese version of ChEHK‐Q and ChEHS‐Q are better than the previous Spanish version (Álvarez‐García et al., 2018) and English version (Álvarez‐García et al., 2020), which means that these two questionnaires can accurately measure the knowledge and skills of nurses in children's environmental health and classify nurses according to their latent traits appropriately.…”
Section: Discussionmentioning
confidence: 82%
“…ChEHK‐Q and ChEHS‐Q were developed by Álvarez‐García et al. (2018), and both of them were verified with good psychometric characteristics and have been widely used in Europe (Alvarez‐Garcia et al., 2020; Álvarez‐García, Álvarez‐Nieto, Kelsey, et al., 2019; Álvarez‐García, Álvarez‐Nieto, Sanz‐Martos, et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sustainable Development Goals (SDG) elements: good health and well-being, clean water and sanitation, and climate actions are interconnected and imperative triangles for reducing neonatal and childhood mortality (9). Globally, the environment contributes to about 13.7 million (24%) deaths, including one in four deaths of children under five years of age and more than a quarter (23%) of disease burdens (10).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental risk factors (foodborne toxins, poor sanitation, dirty home, poor quality cooking fuels, dirty and poor local waste disposal) contribute to stunting in children (14). Additionally, violent behaviors, poor physical growth, and incompetence in mental activities (attention deficit and poor academic performance) are among the long-term impacts of environmental hazards (9).…”
Section: Introductionmentioning
confidence: 99%